2002
DOI: 10.1007/s00737-002-0142-6
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and number of children in patients with Alzheimer's disease

Abstract: Oestrogen therapy has been suggested to have protective effects against Alzheimer's disease. The effects of natural exposure to oestrogen in cognitive disorders have rarely been studied. Assuming that nulliparous women have a higher exposure to natural oestrogen, it could be hypothesised that these women might have a lower risk of Alzheimer's disease than women who have had children. The fertility and number of children in 106 women with a diagnosis of Alzheimer's disease was examined and compared with that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 15 publications
4
50
2
1
Order By: Relevance
“…These findings suggest a mild resistance of the receptor coded by AS/AS genotype to the FSH, which in turn may lead to a subfertility status, as shown by some clinical studies for the AS/AS genotype [19,29]. The observation that the FSHR genotype possibly associated with lower fertility may confer a protection against AD is in line with previous observations that fertility represents a risk factor for AD in women [14,15,16,17,18]. In this case, the role of fertility in AD pathogenesis would be mediated by alterations in hormone levels induced by pregnancy and childbirth [15].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These findings suggest a mild resistance of the receptor coded by AS/AS genotype to the FSH, which in turn may lead to a subfertility status, as shown by some clinical studies for the AS/AS genotype [19,29]. The observation that the FSHR genotype possibly associated with lower fertility may confer a protection against AD is in line with previous observations that fertility represents a risk factor for AD in women [14,15,16,17,18]. In this case, the role of fertility in AD pathogenesis would be mediated by alterations in hormone levels induced by pregnancy and childbirth [15].…”
Section: Discussionsupporting
confidence: 80%
“…Previous investigations have shown that fertility, or genes involved in regulating fertility, may influence AD susceptibility in women [12,13,14,15,16,17,18]. The focus of the present study was to determine a role for FSHR as a potential AD risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that women with 5 or more times of full-term pregnancies had worse cognitive function, compared with those who had fewer times of full-term pregnancies. Previous studies generally supported that despite the high levels of estrogen during pregnancy, women with more parity were associated with the higher risk of cognitive impairment [10][11][12]27] and AD [28][29][30], due to lower circulating estrogen over lifetime than women with fewer parity or nulliparity [25,31]. In contrast, our results is the first to find that women with 3 or more times of incomplete pregnancies were not associated with the decline in cognitive performance compared with women who had fewer times of incomplete pregnancies.…”
Section: Discussionmentioning
confidence: 90%
“…Nous avons retracé quatre études évaluant la fécondité dans les familles où la MA était présente. Heston et al (1981) ainsi que Ptok et al (2002) Notre analyse du rapport de masculinité a révélé des résul-tats intéressants. Les fratries des cas contiennent un excès de filles quand on les compare aux fratries des témoins.…”
Section: Fécondité Et Rapport De Masculinitéunclassified